Dyeing adsorption kinetics of ebtacyanin pigment extracted from hylocereus polyrhizus peel onto spun silk and acrylic yarn - Norasiha, Hamid (2017)
Synthetic dyes that used in textile industry can caused considerable environmental pollution. While, natural dyes are known to be more environmental friendly. Therefore, the study on extraction of natural dyes from plants is currently become revival. In this present work, the natural dye was extracted from dragon fruit peel, also known as Hylocereus polyrhizus, which contains betacyanin pigments. The dyeing adsorption of red-violet betacyanin on the spun silk and acrylic yarn was investigated, where the adsorption mechanisms, adsorption kinetics and thermodynamic parameters as well as the optimum dyeing conditions were determined. The sample analysis was analyzed using UV-Vis spectroscopy in liquid phase. The experimental data were analyzed using Langmuir, Freundlich and Temkin isotherm models and the best-fitted isotherm model was then determined using error analysis. Further investigation on the adsorption kinetic was done using pseudo-first-order and pseudo second-order model to determine the rate constant. For the optimization of dyeing conditions, a systematic experimental design including One-factor-at-a-time (OFAT) and first order model of 25 full factorial designs (FFD) was used in the initial screening process to determine the significant variable factors. The dyeing conditions was optimized using RSM. The best fitting isotherm for both yarns was Freundlich isotherm, which is demonstrated by the highest values of coefficient of determination and was confirmed by three types of error analysis. The adsorption process was followed the pseudo-second-order kinetic model with the rate constant of 0.128 g/min.mg for spun silk and 0.099 g/min.mg at 30°C. By using the rate constant, the activation energies for the spun silk and acrylic yarn adsorption process can be calculated and it was established at 55.7kJ/mol and 44.5kJ/mol respectively. The results of FFD indicated that the pH, dyeing time and dye concentrations are the significant factors for the dyeing conditions with the value of 3, 90 minutes and 100 g/L respectively. These factors were further optimized by RSM and the optimum values obtained for the dyeing conditions were pH 2, 95 minutes dyeing time and dye concentrations of 110 g/L. Under these conditions, the optimum dye uptake at 52.45% was attained. It is confirmed that the overall process of betacyanin pigment adsorption is to be controlled by the chemical adsorption. The thermodynamic parameters such as Gibbs free energy, enthalpy, and entropy were also determined. It can be concluded that the betacyanin pigment adsorption was spontaneous, exothermic and the dye distribution on the surface-active site is randomness. The effect of mordant on the dye uptake was also carried out and it showed that mordants did improve the color properties. This study has demonstrated that the betacyanin pigment can be used as a natural dye and can be applied to the spun silk and acrylic yarn as a coloring agent.